BEJA LEXICOSTATISTICS - Blažek, Václav (Lingua Posnaniensis, 2013)
The Beja (Beḍawye) language is the only representative of the North Cushitic branch of the Cushitic languages. Although there are several dialects, e.g. Amar’ar, Arteiga, Beni Amer, Bishari, Hadendowa, Halenga etc., scholars collecting the lexical data of the Beja language usually do not distinguish between individual dialects and frequently summarize material of two or more dialects (e.g. Reinisch: Beni Amer, Bishari, Hadendowa), or they determine only the area, where their data were collected (e.g. Wedekinds: Eritrea; Hudson: Port Soudan and Tokar). Roper indicated the dialect Hadendowa, but according to MORIN (1995: 22) it was a transitional interdialect of the Sinkat area. In this case it is impossible to separate specific lexicons of individual dialects and the only solution is to compare the lexical materials in dependence, who has collected them. Although there is only one distinctive phonetic isogloss dividing the Beja dialect continuum with typical u in the north vs. i in the south (VANHOVE 2006), the result of the present study demonstrates a relatively high internal diversity of the Beja lexicon. Two most incomplete or deviant sources, namely Munzinger and Bender, indicate the disintegration of common Beja to the 9th and 11th cent. respectively. The common share between the remaining idioms is c. 95% or higher, corresponding to the beginning of their disintegration around AD 1200. This younger dating better agrees with at least partial intelligibility between the tribal dialects of Beja.